Tagabawa bagobo folk narratives structures - JOHN REY A. ALERIA (Journal of Advanced Research in Social Sciences and Humanities, 2020)
Aim: The purpose of this research is to examine the folk tales of the Tagabawa Bagobo, an indigenous group living in the southern Philippines, and to make comparisons and contrasts between their narrative structures. Narratives are aesthetically pleasing because of the careful planning and execution of their syntactic construction. Despite this, there need to be more studies that dissect the narrative architecture of folk tales.Method: This study employs a qualitative approach to inquiry, specifically a descriptive research layout. Tzvetan Todorov, a French-Bulgarian literary theorist, provided the theoretical foundation for this approach, which he called